Comparison of single- and double-spaced feeders with regard to damaging behavior in pigs - D'Alessio, Roberta Maria; Hanlon, Alison; O'Driscoll, Keelin (Frontiers in Veterinary Science, 2023)
This work compared the behavior and performance of 24 groups of 12 pigs kept in pens with either a DOUBLE [one feed space aligned with the front wall of the pen (WALL), and one immediately adjacent (IN)] or SINGLE (WALL only) spaced feeder, from weaning until slaughter. Pens were equipped with a rack of fresh grass and a rubber toy (weaning phase) or a wooden board (finishing phase). Every 2 weeks, interaction with the enrichment, aggressive, harmful, and play behaviors were recorded for 5 min, four times a day. In addition, the pigs were individually assessed every 2 weeks for ear, tail, and flank injuries using a 4-point scale. The duration of feeder occupancy, feed space occupancy, number of and duration of feeding bouts, and aggressive behavior at the feeder were recorded continuously from video recordings (two times while in the weaner stage and two times while in the finisher stage, one camera/pen; 1 h per occasion). Individual body weight was recorded at weaning, transfer, and slaughter, and feed delivery was recorded daily at the pen level; from these measurements, average daily gain, feed intake, and feed conversion ratio were calculated. Data were analyzed using SAS v9.4. There was no effect of treatment on damaging behaviors. Pigs in DOUBLE had worse tail lesion scores on 6 of the 9 recording days (P < 0.001), but values rarely exceeded 1. Total feeder occupancy tended to be longer in DOUBLE than in SINGLE (P = 0.06). DOUBLE selected the IN feed space more often than WALL regarding the number of feeding bouts (P < 0.001). During feeding, pigs in DOUBLE received fewer aggressive behaviors than SINGLE (P < 0.001) and experienced fewer displacements than SINGLE (P < 0.001). Although both experimental groups had a similar weight at slaughter (P > 0.05), the FCR was lower in DOUBLE than in SINGLE (P < 0.05). These data suggest that doubling space at the feeder to two spaces/12 pigs reduced aggression and displacement behaviors at the feeder, indicating less competition for food. However, increasing feeder space was not a management strategy that could ensure reduced tail biting on commercial pig farms.